Analisis Tindakan Eutanasia Dalam Perspektif Hukum Islam dan Kode Etik Kedokteran Indonesia - Lintang Ardiansyah; Muhammad Alwan Fathurrobbanie; Renata Sheehan Del'ara; Desti Septiana; Salman Septiana Rohendi; Rika Widawati (Lembaga Pengembangan Kinerja Dosen, 2024)
Euthanasia, a topic that sparks debate, is a controversial action from both Islamic and medical perspectives. In Islam, honoring human life is considered a paramount value, as emphasized in the Qur'an. Therefore, the practice of euthanasia is seen as incompatible with religious values. In medical practice, ethical codes provide moral guidance emphasizing the importance of protecting human life, thus making this practice also conflicting with these principles. Although some argue that euthanasia can end unbearable suffering, Islamic views stress the importance of preserving human life without hastening death. Therefore, in Indonesia, with a majority Muslim population, euthanasia practices are prohibited based on religious values and applicable laws.